Toward a full aircraft model platform for fuel slosh-structure interaction simulations - Farao, Javon (Department of Mechanical Engineering, 2017)
The purpose of this study was to initiate the development of a full aircraft model (FAM) for the purpose of non-linear loads calculation of an aircraft. The FAM is employed during the design process of an aircraft and comprises of various reduced-order models (ROMs). These are mainly structural, slosh and aerodynamic loads. This study focused on the structural and slosh aspects using Ele- mental(TM) software as the base. First, a structural ROM was developed such that it is compatible with Airbus data and processes. The developed code reads in MSC Nastran data, from which Hermitian finite element discretisation is performed followed by transient calculations. To this end, the structure was represented by Timoshenko beam theory. The structural ROM was validated and verified against the widely used MSC Nastran commercial software. Simulated dynamic responses were within 5% while eigenvalue predictions were within 2% of each other. Secondly, a strongly-coupled partitioned fluid-structure interaction (FSI) scheme was deployed to incorporate the high-fidelity sloshing fluid onto the structure. Lastly, the developed FSI technology was verified and validated against challenging analytical as well as real-world benchmark test cases. It was demonstrated to be accurate and robust in all cases.